SHIP1 Deficiency in Inflammatory Bowel Disease Is Associated With Severe Crohn’s Disease and Peripheral T Cell Reduction - Fernandes, Sandra; Srivastava, Neetu; Sudan, Raki; Middleton, Frank A.; Shergill, Amandeep K.; Ryan, James C.; Kerr, William G. (Frontiers in Immunology, 2018)
In our previous study, we observed a severe reduction in the Src Homology 2-containing-inositol-phosphatase-1 (SHIP1) protein in a subpopulation of subjects from a small adult Crohn’s Disease (CD) cohort. This pilot study had been undertaken since we had previously demonstrated that engineered deficiency of SHIP1 in mice results in a spontaneous and severe CD-like ileitis. Here we extend our analysis of SHIP1 expression in peripheral blood mononuclear cells in a second much larger adult Inflammatory Bowel Disease (IBD) cohort, comprised of both CD and Ulcerative Colitis patients, to assess contribution of SHIP1 to the pathogenesis of human IBD. SHIP1 protein and mRNA levels were evaluated from blood samples obtained from IBD subjects seen at UCSF/SFVA, and compared to them healthy control samples. Western blot analyses revealed that ~15% of the IBD subjects are severely SHIP1-deficient, with less than 10% of normal SHIP1 protein present in PBMC. Further analyses by flow cytometry and sequencing were performed on secondary samples obtained from the same subjects. Pan-hematolymphoid SHIP1 deficiency was a stable phenotype and was not due to coding changes in the INPP5D gene. A very strong association between SHIP1 deficiency and the presence of a novel SHIP1:ATG16L1 fusion transcript was seen. Similar to SHIP1-deficient mice, SHIP1-deficient subjects had reduced numbers of circulating CD4+ T cell numbers. Finally, SHIP1-deficient subjects with CD had a history of severe disease requiring multiple surgeries. These studies reveal that the SHIP1 protein is crucial for normal T cell homeostasis in both humans and mice, and that it is also a potential therapeutic and/or diagnostic target in human IBD.